Factors Affecting Employee Performance during Work from Home - Aropah, Vina Da’watul; Sarma, Ma’mun; Sumertajaya, I Made (International Research Journal of Business Studies, 2020)
The Corona Virus Disease (Covid-19) pandemic in Indonesia began with the discovery of Covid-19 sufferers on March 2, 2020. Coronavirus is a group of viruses that can cause disease in animals or humans. To respond the conditions of the Covid-19 outbreak, NPPA issued a regulation concerning adjustments to the work system of the government employee in efforts to prevent the spread of Covid-19. This study uses census sampling, where all members of the population used as samples. The total responden of the Government Employee in NPPA is 128 employees, who are works mostly at home during the pandemic. The research data used primary and secondary data. Comparison using PLS-SEM as analyzing the data. The result of the research showed that leadership and work environment have impact on employee performance, whereas organizational support has no impact on employee performance.